2001
DOI: 10.1053/rapm.2001.19638
|View full text |Cite
|
Sign up to set email alerts
|

Selective ulnar nerve localization is not essential for axillary brachial plexus block using a multiple nerve stimulation technique

Abstract: A triple-injection method of axillary block in which the ulnar nerve was not purposely located provides a spread and a latency of sensory block equal to that obtained with a 4-injection technique. A shorter performance time is an advantage of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…2 Using the same mixture as for ICB, 14, 14, and 7 mL were injected to anesthetize the median, radial, and musculocutaneous nerves, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…2 Using the same mixture as for ICB, 14, 14, and 7 mL were injected to anesthetize the median, radial, and musculocutaneous nerves, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple nerve stimulation axillary block is a wellestablished technique that is associated with a high success rate of anesthesia of the upper limb at or below the elbow [2][3][4][5][6]. However, multiple nerve stimulation requires a longer time to complete and has a potentially higher risk of developing postanesthetic nerve injury [7].…”
Section: Discussionmentioning
confidence: 99%
“…Sia et al found comparably high success rates of 90% and 92% for successful blocks of the ulnar nerve in a nerve stimulator guided study on AXB with multiple injections. 49 The authors could also demonstrate that a selective block of the ulnar nerve in one of the study groups did not increase the block success rate. Tran et al had comparable success rates in ultrasound guided double-, triple-and quadruple-injection techniques and did not achieve higher success rates for the ulnar nerve when it was selectively blocked.…”
Section: Block Experiences For Single Nervesmentioning
confidence: 91%